Efforts to Improve the Quality of Islamic Religious Education Through the Contextual Teaching and Learning (CTL) Model in the Qur'an Reading and Writing (BTQ) Material - Ahmad Mubarok; Munawaroh; Saepudin; Mifatahudin; Sanin Sudrajat; M. Asep Rahmatullah (IAIN KENDARI, 2025)
This study investigates the implementation of the Contextual Teaching and Learning (CTL) model to improve the quality of Islamic Religious Education, specifically in the Qur’an Reading and Writing (BTQ) subject at SDN Kebaharan 1, Serang City. Employing a classroom action research design, the research involved fourth-grade students and aimed to enhance their learning outcomes through contextual and meaningful learning experiences. The results indicate a significant improvement in students’ academic performance, from a pre-cycle average of 47.8 to 73.24 in the second cycle, with 100% of students achieving the minimum mastery criteria. The CTL model successfully engaged students in active, reflective, and collaborative learning processes by linking Qur’anic content to their everyday lives. Furthermore, it fostered the development of cognitive, affective, and psychomotor skills, while strengthening religious character. The study concludes that CTL is an effective and relevant approach in Islamic Religious Education and should be further developed in elementary school curricula to promote holistic learning.